PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP INTEGRITAS LAPORAN KEUANGAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI (Studi Empiris Pada Perusahaan Badan Usaha Milik Negara Yang Terdaftar Di Bursa Efek Indonesia Periode 2017-2019) - Putri Kasih Shaumi Dwi; DP Nur Emrinaldi; Hasan Alamsyah Mudrika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This research aims to examine the impact of good corporate governance (institutional ownership, independent commissioners, and audit committee) on the integrity of financial statements with firm size as a moderating variable. The object of this research is state-owned enterprises on the Indonesian Stock Exchange (BEI) period 2017-2019. In this research there were 20 enterprises as population, but based on the criteria of only 17 enterprises so there were 51 samples in this research. The sampling technique used in this research is purposive sampling method. The data used in this research are secondary data, namely the annual report obtained through the IDX website. Data analysis method using moderated regression analysis or interaction test. The results showed that institutional ownership had a significant impact on the integrity of financial statements with a significance value of 0,000 < 0,05, independent commissioners had a significant impact on the integrity of financial statements with a significance value of 0,017 < 0,05, audit committee had a significant impact on the integrity of financial statements with a significance value of 0,022 < 0,05, firm size was able to moderate the impact of the institutional ownership on the integrity of financial statements with a significance value of 0,003 < 0,05, firm size was able to moderate the impact of the independent commissioners on the integrity of financial statements with a significance value of 0,021 < 0,05, and firm size was not able to moderate the impact of the audit committee on the integrity of financial statements with a significance value of 0,093 > 0,05.Keywords: institutional ownership; independent commissioners; audit committee; firm size; integrity of financial statements